PENGARUH TINGKAT KERUSAKAN JALAN, PERGERAKAN LALU LINTAS, DAN KECEPATAN KENDARAAN TERHADAP TINGKAT KECELAKAAN DI RUAS JALAN PUNGGALUKU-ANDOOLO KABUPATEN KONAWE SELATAN - Harto Harto (Jurnal Manajemen Rekayasa (Journal of Engineering Management), 2021)
The purpose of this study was to determine and analyze the effect of the level of road damage, daily traffic and vehicle speed on accident rates on the Puunggaluku-Andoolo road section. This type of research is explanatory, descriptive-quantitative in nature. The population in this study were all people who crossed or used the Punggaluku-Andoolo road using two wheels, four wheels and trucks. The sample set in this study is the Punggaluku-Andoolo road section that is divided into 20 observation points. Each variable is analyzed by a different method, the variable level of road damage is analyzed using the PCI method, the variable traffic flow uses the daily traffic (LHR) method while the vehicle speed variable is measured by using a stopwatch tool to get the average speed of each each segment was observed, which was then analyzed using the SPSS 26.0 IMB program in linear regression to see its effect on the vehicle accident rate variable.The results of this research are: (1). The level of damage to the roads in the Pungguluku-Andoolo Road, Konawe Selatan district, on average of the 20 segments observed was in the range of 54.3 values based on the Moderate categorized PCI analysis, while for the daily traffic volume analysis of 788 junior high schools that passed , and an average vehicle speed of 63.98 km / hour; (2). The variable road damage has a negative and not significant effect on the level of vehicle accidents on the Punggaluku-Andoolo road section in Konawe Selatan district; (3) The variable of the movement of traffic flow has a negative but significant effect on the level of vehicle accidents on the Punggaluku-Andoolo road section in Konawe Selatan regency; (4). Vehicle speed variable has a positive but not significant effect on the level of vehicle accidents on the Punggaluku-Andoolo road section in Konawe Selatan district.